Breast Cancer in Elderly Females (American Journal of Medical Science and Innovation, 2023)
Breast cancer develops when the breast’s cells multiply uncontrollably. Breast cancer ranks as the second leading cause of cancer-related mortality among women. Breast cancer risk increases with age. Almost 1 in 7 women will experience the onset of breast cancer during their lifetime. Breast cancer is a malignant or cancerous tumour that develops from cells in breast tissue. Although they are non-life-threatening and confined to the breast, some women develop benevolent or non-cancerous breast lumps. Many people are unaware they have breast cancer since the early stages of the disease are frequently benign. Early discovery provides more time for evaluation and treatment, which can help prevent negative effects. Self-examination and several diagnostic tools as mammography, ultrasound, and nuclear medicine, are used to evaluate invasive and non-invasive breast cancer. Several therapies associated with breast cancer treatments include chemotherapy, radiation therapy, hormone therapy, and bone-directed therapy. Surgeries can also effectively treat breast cancer, such as lumpectomy and mastectomy. This suggests that effective therapies are progressing. This review aims to determine breast cancer’s causes, prevalence, and treatments in elderly women. The authors have discussed the disease’s treatment criteria and protocols, such as pharmacological therapies, herbal treatment, lifestyle modifications, and physical activities